Risk of Thrombosis, Pregnancy Morbidity or Death in Antiphospholipid Syndrome - Killian, Martin; van Mens, Thijs E. (Frontiers in Cardiovascular Medicine, 2022)
The antiphospholipid syndrome is an autoimmune disease characterized by thrombosis and pregnancy morbidity. The manifestations are caused by antibodies targeting cell membrane phospholipids and/or associated proteins. The triggers leading to these antibodies’ production are unknown but recent work suggests cross-reactivity between the autoantigens and peptides produced by the intestinal microbiome. Work on how the autoantibodies could cause clinical manifestations implicates different mechanisms. Binding to surface proteins of different cell types can induce intracellular signaling leading to cell activation and tissue factor expression. Complement activation and neutrophil extracellular-traps are also involved, and recent evidence implicates endothelial protein C receptor-lysobisphosphatidic acid complex. Pregnancy is a high-risk situation for antiphospholipid syndrome patients due to the increased risk of thrombosis and obstetric complications. Epidemiological and clinical research on APS is hampered by heterogeneity in populations, testing and treatment strategies. About one in ten to one in fifty APS pregnancies is complicated by thrombosis, despite treatment. Pregnant patients with prior thrombosis are prescribed therapeutic dose heparins and low dose aspirin. Without prior thrombosis a prophylactic dose is used. The most frequent obstetrical manifestation is recurrent early pregnancy loss. The association of APS antibodies with late pregnancy loss is stronger, however. Prevention of recurrence is achieved with aspirin and prophylactic dose heparin, although the evidence is of low certainty. The third obstetrical classifying manifestation comprises preterm delivery due to placenta-mediated complications and is treated in subsequent pregnancies with aspirin with or without prophylactic dose heparin, again based on low quality evidence. New therapies are under investigation.